In vivo anticoccidial effects of Beta vulgaris (sugar beet) in broiler chickens. (October 2017) - Abbas, Asghar; Iqbal, Zafar; Abbas, Rao Zahid; Khan, Muhammad Kasib; Khan, Junaid Ali; Sindhu, Zia ud Din; Mahmood, Muhammad Shahid; Saleemi, Muhammad Kashif
Abstract: Recently, use of botanicals as an alternative to anticoccidial drugs has been appealing approach for controlling avian coccidiosis. Therefore, this study was conducted to evaluate the anticoccidial activity of aqueous methanolic extract (100, 200 and 300 mg/kg of body weight) of Beta vulgaris (roots) in broiler chicks. A total of 315 day old broiler chicks were divided into seven equal groups (A, B, C, D, E, F and G). At 14th day of age, all groups except group G, which served as non infected non medicated control, were infected orally with 60, 000 sporulated oocysts of mixed Eimeria species. At the same day, groups A, B and C were treated with graded oral doses of B. vulgaris aqueous methanolic extract (100, 200 and 300 mg/kg of body weight, respectively). Group D was treated with Vitamin-E, group E served as infected medicated control group (Baycox ® treated) and group F served as infected non medicated control group (PBS treated). Treatment with extract, reference drug Baycox ®, Vitamin E and PBS was continued for three consecutive days (14–16 days of age). Though, not at par with reference drug (Baycox ® ), B. vulgaris demonstrated good anticoccidial activity adjudged based on considered criteria, i.e., feed conversion ratio, lesion score, oocyst score and oocysts per gram of feces. Results of serum profile of infected chicks revealed no adverse effects of aqueous methanolic extract of B. vulgaris on the experimental chicks. Highlights: Drug resistance in Eimeria species has motivated poultry scientists to search alternatives to anticoccidial drugs. Among alternatives, antioxidant rich botanicals have been appealing approach. Beta vulgaris extract has shown promising results in controlling caecal coccidiosis in broiler chickens.